Stress And Anxiety Levels Of Correctional Assisted Patients At Class 1 Rutan Clinic, Central Jakarta Against The Spread Of Covid-19 And Its Review From An Islamic Perspective - Fildza Sabhrina Dharmawan; Edward Syam; Muhammad Arsyad (Junior Medical Journal, 2022)
Background: As of March 11, 2020, the World Health Organization (WHO) designated COVID-19 to be a global pandemic disease. COVID-19 was initially discovered in Wuhan, Hubei, China in December 2019. People are ill-equipped, both physically and mentally, to handle this abrupt predicament. When infected, the population goes through a number of psychological ailments, including anxiety. Research on Stress and Anxiety Levels on the Spread of COVID-19 in Correctional Assisted Patients at the Class 1 Central Jakarta Rutan Clinic is considered significant because, in a pandemic like this, it is crucial to understand the mental health of prisoners and this research has never been done before.Method: Using a cross sectional research approach, this kind of study makes descriptive observations. 352 participants from the Class 1 Rutan Clinic in Central Jakarta and 2,900 correctional service patients made up the study's sample pool. Questionnaires and direct interviews with respondents are two data collection methods. Univariate and bivariate analysis are the two types of analysis used in this study.Result: The mild category had 198 respondents, which had the highest incidence of stress out of the 352 respondents. As many as 172 respondents said they felt the most anxiety in the moderate category. The Chi-Square statistical test revealed no correlation between stress and anxiety levels and the COVID-19 outbreak.Conclusion:  In the Class 1 Central Jakarta Rutan Clinic's COVID-19 prevention program, patients receiving correctional assistance have mild to moderate stress levels and moderate to high levels of anxiety. To avoid tension and anxiety, Allah SWT commands us to think positively and to practice moderation.